The Concept of Rwa Bhineda within the Balinese Hindu Society - Kapela, I Made Ari (Bali Tourism Board, 2023)
Humans possess intelligence and consciousness to interact with their surrounding environment. This cognitive ability allows humans to contemplate, communicate, and participate in activities with others. The dynamic interplay of opposing forces, evident in the realms of positive and negative, joy and sorrow, is intricately woven into the fabric of Hindu thought. The concept of Rwa Bhineda extends metaphorically to encompass the entire spectrum of human experience, symbolizing the harmonious coexistence of contrasting elements. The Black and White characteristic regions within Rwa Bhineda, though seemingly contradictory, are inherently connected, mutually sustaining and weakening one another. This duality is not a source of conflict but rather a foundation for harmony, development, and progress. Furthermore, the application of Rwa Bhineda in Balinese local wisdom provides practical solutions to global challenges, emphasizing the importance of balance and harmonious coexistence amid differences. The Balinese cultural philosophy, encapsulated in concepts like Tri hita karana and Rwa Bhinedha, serves as a foundation for tolerance and diversity within Hindu religious practices. The celebration of Purnama and Tilem in the Balinese Wariga system symbolizes this concept, serving as reminders of life's inherent dualities and the potential for harmony through their complementary nature. Thus, the profound wisdom embedded in Rwa Bhineda offers a valuable perspective on navigating the complexities of human existence with grace and understanding.